2013
DOI: 10.1111/j.1365-2702.2012.04317.x
|View full text |Cite
|
Sign up to set email alerts
|

Motivational interviewing and exercise programme for community‐dwelling older persons with chronic pain: a randomised controlled study

Abstract: Motivational interviewing is a feasible counselling technique whose content can be modified based on target group to change maladaptive behaviours, elicit ambivalences and enhance self-efficacy for making changes. Thus, promoting motivational interviewing and physical exercise programme to older persons with pain is effective and important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
55
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 68 publications
(117 reference statements)
3
55
0
2
Order By: Relevance
“…The clinical studies reported in this review were performed in different countries: USA (Poleshuck et al, 2014;Lattie et al, 2013;Nash et al, 2013;Darchuk et al, 2010;Unützer et al, 2008;Field et al, 2007); Republic of Ireland (Fullen et al, 2013); United Kingdom (McCracken, Sato & Taylor, 2013); Sweden (Taloyan, Alinaghizadeh & Löfvander, 2013;Bremander, Holmström & Bergman, 2010); Singapore (Tan et al, 2013); China (Tse, Vong & Tang, 2013); Denmark (Frich et al, 2012);…”
Section: Participantsmentioning
confidence: 99%
See 4 more Smart Citations
“…The clinical studies reported in this review were performed in different countries: USA (Poleshuck et al, 2014;Lattie et al, 2013;Nash et al, 2013;Darchuk et al, 2010;Unützer et al, 2008;Field et al, 2007); Republic of Ireland (Fullen et al, 2013); United Kingdom (McCracken, Sato & Taylor, 2013); Sweden (Taloyan, Alinaghizadeh & Löfvander, 2013;Bremander, Holmström & Bergman, 2010); Singapore (Tan et al, 2013); China (Tse, Vong & Tang, 2013); Denmark (Frich et al, 2012);…”
Section: Participantsmentioning
confidence: 99%
“…ü Physical exercise (Lattie et al, 2013;Taloyan, Alinaghizadeh & Löfvander, 2013;Tse, Vong & Tang, 2013;Bremander, Holmström & Bergman, 2010;Darchuk et al, 2010);…”
Section: );mentioning
confidence: 99%
See 3 more Smart Citations